Monuments & memory: Christian cult buildings and constructions of the past : essays in honour of Sible de Blaauw - Verhoeven, Mariëtte; Bosman, Lex; Asperen, Hanneke van (Architectural crossroads, 2016)
Essays on the memorial potential of Christian buildings, of their location, or of the accoutrement, whether or not still in situ, with a special attention to Rome's churches. The contributions in this volume are divided in three main sections: Monuments, Places, and Decoration & Liturgical Furnishing. Every essay addresses the memorial potential of Christian buildings, of their location, or of the accoutrement, whether or not still in situ. Not surprisingly Rome re-appears frequently in all sections, with special attention to Rome's churches.